Strategy To Increase Culinary MSMEs Sales Through Online Food Delivery - Riski Pratama Putra; Angga Ramadani; Yulianti Sari Hutabarat; Lambok Manurung (Outline Publisher, 2025)
Medan Timur, a district in Medan, North Sumatra, is home to a rapidly growing culinary industry, with numerous micro, small, and medium-sized enterprises (MSMEs) utilizing online food delivery services such as GoFood, GrabFood, and ShopeeFood. This research aims to analyze the impact of online food delivery services on the sales growth of culinary MSMEs in the area. Using a qualitative approach, data were collected through observations, interviews, and a literature review from five culinary business owners who have joined these platforms. The findings reveal that nearly all MSMES that joined the platforms experienced significant sales increases, with daily income rising by an average of 150% to 200%. Additionally, MSMEs gained other benefits, such as enhanced business visibility and broader customer access without additional advertising costs. The study also identifies technical challenges faced by some MSMEs, such as payment and transaction management issues, which were resolved with platform support. Overall, the research shows that online food delivery apps play a crucial role in helping culinary MSMEs in Medan Timur thrive, expanding their market reach and increasing their revenues.